2014
DOI: 10.1590/1519-6984.21912
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fish farming in net cages on phytoplankton structure: a case study in a subtropical Brazilian reservoir

Abstract: This study investigated the enrichment influence due to fish farming in net cages on the phytoplankton composition, density and diversity in two arms of a subtropical reservoir (Salto Caxias, Paraná). There were no statistically significant differences in the phytoplankton composition and diversity, as well as for concentrations of nutrients among the handled treatment. The density values were higher during the summer. Richness and Shannon diversity values were low during the study period. The equitability val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…The mean pH values observed in this study remained within of the ideal range (between 6.5 and 9.0) for fish production (Baldisserotto, 2002). Other authors evaluated the influence of net cages fish farms on water quality and also observed that the pH remained close to neutrality and within the standard limits established by CONAMA 357/05 legislation (Bueno et al, 2008;Américo et al, 2012;Mallasen et al, 2012;Bartozek et al, 2014). The similarity of mean pH values found in this study shows that the fish farming did not affect this variable in Furnas reservoir.…”
Section: Resultssupporting
confidence: 82%
“…The mean pH values observed in this study remained within of the ideal range (between 6.5 and 9.0) for fish production (Baldisserotto, 2002). Other authors evaluated the influence of net cages fish farms on water quality and also observed that the pH remained close to neutrality and within the standard limits established by CONAMA 357/05 legislation (Bueno et al, 2008;Américo et al, 2012;Mallasen et al, 2012;Bartozek et al, 2014). The similarity of mean pH values found in this study shows that the fish farming did not affect this variable in Furnas reservoir.…”
Section: Resultssupporting
confidence: 82%
“…According to PCA results, the analyzed abiotic variables were influenced by seasonality. Other authors also pointed out seasonality as one of the factors influencing variations in abiotic factors, mainly water transparency, in studies similar to the current one (Alves and Baccarin, 2005;Borges et al, 2010;Kaggwa et al, 2011;Ayroza et al, 2013;Bartozek et al, 2014).…”
Section: Resultssupporting
confidence: 61%
“…Bueno and Shimizu (2008) performed an extensive revision of the factors responsible for the interspecific variation on the reproductive period of aeglids and suggest that the reproductive period tends to be concentrated in the colder months of the year at lower latitudes, as is the case in the present study. Besides, subtropical regions have seasonal changes in rainfall and induce physical and chemical changes in water (Figueredo and Giani, 2001;Bartozek et al, 2014) that may contribute to this pattern.…”
Section: Discussionmentioning
confidence: 99%